Perspectives On Mobility, Migration And Well-being Of International Students In The Asia Pacific - Kell , Peter; Vogl, Gillian (Penerbit Universiti Sains Malaysia (USM Press), 2008)
This edition of the International Journal of Asia Pacific Studies explores issues relating to global student mobility in the Asia Pacific. The contributions to this edition from Australia and Malaysia emerged from a forum held in Australia in February where academics and researchers from Malaysia, China, Singapore and Australia presented papers and discussed ways of interpreting the character and the implication of global student mobility. The forum entitled International Students in the Asia Pacific: Mobility, Migration, Well-being and Security held from 13–15th February 2008 attracted over 40 presenters. The forum was hosted by the Centre for Asian Pacific Social Transformation Studies at the University of Wollongong and was part of a continuing research partnership between the Universiti Sains Malaysia, the University of Wollongong and a growing number of Australian and Malaysian researchers